High prevalence of insulin resistance and occurrence prior to hyperinsulinemia threshold among people living with HIV in Pune, India. Issue 3 (May 2019) - Marbaniang, Ivan; Sangle, Shashikala; Salvi, Sonali; Kulkarni, Vandana; Shere, Dhananjay; Deshpande, Prasad; Nimkar, Smita; Gupta, Amita; Mave, Vidya
Abstract: Background: Diabetes prevalence in HIV is not well characterized for India, despite the high burden of both individual diseases. Epidemiology of insulin resistance (IR): a precursor to diabetes, and its associated risk factors are also poorly understood in Asian Indian people living with HIV (PLHIV). We assessed the prevalence of diabetes and IR in Pune, India and the associated risk factors for IR. Methods: Cross-sectional analysis of adult (≥18 years) PLHIV receiving care at Byramjee Jeejeebhoy Government Medical College and Sassoon General Hospitals, Pune, India (BJGMC- SGH). Proportions and medians of PLHIV characteristics by diabetes status and IR were described. Homeostatic Model Assessment (HOMA) index value ≥2 was used to define IR. Line of least squares assessed the relationship between IR and hyperinsulinemia. Association between sociodemographic, clinical factors with IR was determined using logistic regression. Results: Of 485 enrollees, 47% were men, median age was 40 years (IQR: 35–46), median CD4 counts were 389 cells/mm 3 (246–609). Thirty-five percent were centrally obese, 75% were adherent to WHO recommended physical activity guidelines. Prevalence of diabetes, prediabetes, IR were 9%, 16% and 38%, respectively. Twenty-nine percent non-diabetics had IR and it occurred much prior to the threshold for hyperinsulinemia. IR was associated with the use of ART drugs (OR: 6.6, 95% CI: 2.9–15.2 and 5.4, 95% CI: 2.2–13.6 for first- and second line ART respectively) and central obesity (OR:1.9, 95% CI: 1.1–3.4). Conclusions: One fourth of the study population was diabetic or prediabetic and more than a third had IR. Better understanding of diabetes disease progression in relation to IR and the effect of physical activity on central obesity among Asian Indian PLHIV is mandated.